The Work-Related Basic Need Satisfaction Scale: An Italian Validation - Colledani, Daiana; Capozza, Dora; Falvo, Rossella; Di Bernardo, Gian Antonio (Frontiers in Psychology, 2018)
The main goal of the present study was to validate the Work-related Basic Need Satisfaction (W-BNS) scale in the Italian social context. Three studies were carried out. Study 1 was conducted on two samples of employees. Exploratory factor analysis and parallel analysis were run on the first sample, whereas confirmatory factor analyses were run on the second. Results supported the three-dimensional structure of the W-BNS scale. Study 2 was conducted on a third sample of employees. Results supported the construct validity of the scale, by showing that needs for competence, autonomy, and relatedness were associated with job resources (social support, job autonomy, professional growth), low burnout, and job attitudes (job satisfaction, turnover intentions, commitment). In addition, results showed that responses to the scale were not affected by social desirability bias. Study 3 was conducted to evaluate the nomological validity of the scale (the sample grouped together all respondents from Studies 1 and 2). A model was tested in which organizational commitment mediated the relationship between basic needs and two outcomes (job satisfaction, intentions to leave). Organizational commitment was measured by using the Klein et al. Unidimensional Target-free scale (the KUT). Results supported the nomological validity of the scale. In line with our expectations, the three needs were associated with the KUT, which in turn mediated the effects of needs on the outcomes. Practical implications of findings and directions for future research are discussed.